2019
DOI: 10.1021/acs.jafc.9b01037
|View full text |Cite
|
Sign up to set email alerts
|

Potential Link between Gut Microbiota and Deoxynivalenol-Induced Feed Refusal in Weaned Piglets

Abstract: This study investigated the potential link between gut microbiota and deoxynivalenol (DON)-induced feed refusal. A total of 24 barrows were randomly divided into one of three diets containing 0.61 (control diet), 1.28, or 2.89 mg DON/kg feed for 28 days. Dietary exposure to DON at 2.89 mg/kg significantly decreased the relative abundances of unclassified_f_Lachnospiraceae, Phascolarctobacterium and Ruminococcaceae_UCG-014, whereas it increased Prevotella_9 and norank_f_Prevotellaceae in the cecal digesta. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…In the present study, the change in PYY gene expression may be related to the increased SCFAs levels. PYY has been shown to induce satiety by upregulation of anorexigenic signal pathway and downregulation of orexigenic signaling molecule neuropeptide tyrosine in the hypothalamus, which is associated with food intake of pigs (Wang et al, 2019a). Thus, the increased SCFAs production and PYY gene expression may be an important reason for the reduced feed intake in the weaning transition.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the change in PYY gene expression may be related to the increased SCFAs levels. PYY has been shown to induce satiety by upregulation of anorexigenic signal pathway and downregulation of orexigenic signaling molecule neuropeptide tyrosine in the hypothalamus, which is associated with food intake of pigs (Wang et al, 2019a). Thus, the increased SCFAs production and PYY gene expression may be an important reason for the reduced feed intake in the weaning transition.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota plays an important role in suppressing pathogen infection and regulating nutrient digestion and absorption and closely shapes intestinal barrier function [ 24 ]. Although numerous studies have shown a deleterious effect of DON exposure on the gastrointestinal tract, only a few studies have investigated the effect of DON on the intestinal microbial ecosystem of piglets [ 25 , 26 ]. Furthermore, whether DON induces intestinal damage and growth inhibition in piglets by altering the gut microbiota remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are secondary metabolites produced by fungi, which are capable of causing noxious effects on humans and animals [10,11]. Increased investigations on mycotoxins, such as aflatoxin B1 [12,13], deoxynivalenol [14,15], zearalenone [16], trichothecene [17], etc., have proved that exposure of mycotoxins could influence the diversity and composition of gut microbiome. Meanwhile, the intestinal bacterial flora has the ability to bind, degrade or Toxins 2021, 13, 612 2 of 14 transform mycotoxins [18,19].…”
Section: Introductionmentioning
confidence: 99%